Plebeia catamarcensis and Tetragonisca fiebrigi (Hymenoptera, Apidae) propolis promotes longevity and anti-Alzheimer effects in Caenorhabditis elegans - Kamila dos Santos Arteman; Paola dos Santos da Rocha; Daniel Ferreira Leite; Alex Santos Oliveira; Igor Victor da Silva; Natalia Guedes Jorge; Alércio da Silva Soutilha; Helder Freitas dos Santos; Debora da Silva Baldivia; José Benedito Perrella Balestieri; Claudia Andrea Lima Cardoso; Kely de Picoli Souza; et al. (PLoS ONE, 2025)
Alzheimer’s disease is a neurodegenerative condition associated with oxidative stress, affecting millions of people worldwide, with expected increases due to the aging population. The development of efficient therapies is still challenging. Propolis, with its antioxidant properties, shows potential in controlling the oxidative stress associated with the disease. The present study aimed to determine the chemical composition of ethanolic extract from propolis produced by Plebeia catamarcensis (EEP-Pc) and Tetragonisca fiebrigi (EEP-Tf), as well as their in vitro and in vivo antioxidant effects, lifespan influence and induced paralysis in Caenorhabditis elegans, mutant model for Alzheimer’s disease. The chemical profile of EEP-Pc and EEP-Tf was characterized through GC-MS and HPLC, identifying phenolic compounds and terpenes. In vitro antioxidant activity was observed using the DPPH• free radicals scavenging method and protection against proteins and DNA oxidation. In vivo, P. catamarcensis and T. fiebrigi propolis extracts showed no reproductive or locomotor toxicity and promoted resistance to oxidative stress in nematodes exposed to the oxidative agent Juglone. Both propolis extracts increased longevity and reduced the signs of paralysis caused by the accumulation of β-amyloid peptides, a marker for Alzheimer’s disease. Together, these data show that propolis from stingless bees P. catamarcensis and T. fiebrigi exhibits promising antioxidant activities against oxidative stress, indicating pharmacological potential with the capacity to reduce symptoms of Alzheimer’s disease.